Deepening Intraregional Trade and Investment in South Asia: The Case of the Textiles and Clothing Industry - Meenu Tewari (Indian Council for Research on International Economic Relations (ICRIER), 2008)
This paper draws on recent field work within South Asia and an extensive review of secondary data to examine the dynamics of cross border trade and investment in South Asia, exploring the potential for, and obstacles to, such trade through the lens of a sector that is salient throughout South Asia: Textiles and Clothing. Despite the growing competitiveness of this sector in the SAARC region, there is very little regional inter-linkage within South Asia's textile and clothing industry. Currently less than 4 of SAARC's global T&C exports are traded within the region. There is growing evidence of widespread substitution of South Asia by East Asia as the sourcing hub of fabric and accessories by the region's major clothing exporters. Over 80 of the fabric needs of Bangladesh and Sri Lanka, for example, come from outside the region even though India and Pakistan are net exporters of textiles. At one level the history of external ties matters: the long standing role of East Asian suppliers and quota-hopping garment manufacturers in the origin of apparel exports in parts of South Asia, the institutional embedding or `bundling' of sourcing practices and input supply, as well as the role of global buyers in designating or mandating preferred input and accessory suppliers have all generated inertia in altering existing relationships. At another level, the burden of mistrusts embedded in the region's own history, the structure of its textile industry (narrowly cotton-based, not very diverse, relatively high cost), and high trade costs exacerbated by complicated rules of origin, frustrating layers of bureaucratic and administrate oversight, poor transportation, and a long list of non-tariff barriers that disrupt the movement of goods and personnel across South Asia have prevented the emergence of either a common market or regional production networks in the SAARC region. Despite these barriers, there is growing evidence that with recent shifts in the nature of the textile and clothing industry, especially post-MFA, as well as changing intra-regional dynamics there are emerging possibilities for cooperation and collective action in the region. The drivers of this potential lie in the growing importance of the domestic market and the rise of organized retail in South Asia, the rise of a new generation of younger entrepreneurs in South Asia who are increasingly professional, globally aware, and schooled in a shared cultural worldview that helps cut across traditional barriers of region and history, the emergence of new knowledge networks and an interpenetrated regional labor market in skills in the South Asian garment industry and the possibility of leveraging strategic regulatory shifts and upcoming `demands for structural change' post-2008 to foster greater regional cooperation. The paper argues that SAARC members - along with civic organizations and private sector industry associations - need to build upon and support the positive trends already underway. In addition, SAARC could enhance interregional integration in textiles and clothing by creating the conditions for greater cross-border investment within the SAARC region, first in textiles and accessories and then apparel, by expeditiously establishing a credible investment protocol in the region, while simultaneously pushing forward with trade facilitation reforms. India, in its current role as SAARC Chair should take a leading role in facilitating these reforms.
Keywords: F15; F14; F59; 330; South Asia; Trade; Investment; Textile and clothing; Regional Cooperation.; Regionale Wirtschaftsintegration; Auslandsinvestition; Textilindustrie; Internationale Wirtschaftsbeziehungen; SAARC-Staaten; Südasien